Model STAD Berbantuan Flashcard Pakyno sebagai Alternatif Inovasi Pembelajaran Matematika - Safitri, Aka Dewi; Putra, Lisa Virdinarti (Lembaga Yasin AlSys, 2025)
This research aims to analyze the influence of the Student Team Achievement Division (STAD) learning model assisted by Pakyno Flashcard media on students' understanding of concepts. The research uses a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects were class IV students at SD Negeri Klepu 05 Pringapus, where class IV A was used as the experimental group and class IV B as the control group. Data was collected through concept understanding tests, observations, and questionnaires. The results showed that there was a significant difference between the experimental group and the control group with a sig value = 0.001 (< 0.05). The average understanding of students' concepts in the experimental class reached 95.08, higher than the control class which obtained an average of 90.42. In addition, the results of a simple linear regression test show that the STAD learning model assisted by Flashcard Pakyno media has an influence of 24.5% on students' understanding of concepts. This research concludes that the application of the STAD model with the support of Pakyno Flashcard media is effective in increasing students' understanding of concepts.